Pengaruh Pelatihan dan Pengembangan Sumber Daya Manusia terhadap Kinerja Karyawan PT Pagi Ceria Indonesia Lenteng Agung Barat - Muhammad Riko Wahyunianto; Ratnawaty Marginingsih; Wiwit Rohaeni Yulianti (STIKes Ibnu Sina Ajibarang, 2025)
PT Pagi Ceria Indonesia is one of the companies engaged in Gardening and Services to serve landscape needs. In managing human resources, PT Pagi Ceria Indonesia needs to pay attention to training and development of each employee in order to produce quality employees and superior performance.. This study aims to determine the effect of training and development of human resources on the performance of employees of PT Pagi Ceria Indonesia in Lenteng Agung Barat. The research method used is a quantitative method with data collection using total sampling or non-probability sampling. A total of 50 respondents were sampled and the data obtained using SPSS 23 software with multiple linear regression analysis techniques including instrument testing, partial and simultaneous hypothesis testing. The results of the Training Variable (X1) research have a significant effect on Employee Performance, with a calculated t value of 3.275 > t table 2.013 and a significance value of 0.002 < 0.05. The results of the Human Resource Development Variable (X2) also have a significant effect on Employee Performance, with a calculated t value of 3.944 > 2.013 and a significance value of 0.000 < 0.05 and the results of the F test (simultaneous), with calculated F = 57.916 > F table = 3.20 and Sig. = 0.000 < 0.05 shows that Training and Human Resource Development together have a significant effect on Employee Performance at PT Pagi Ceria Indonesia.